The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2015
DOI: 10.1177/0886260515572472
|View full text |Cite
|
Sign up to set email alerts
|

Harsh Parenting As a Potential Mediator of the Association Between Intimate Partner Violence and Child Disruptive Behavior in Families With Young Children

Abstract: Young children living with intimate partner violence (IPV) are often also exposed to harsh parenting. Both forms of violence increase children’s risk for clinically significant disruptive behavior, which can place them on a developmental trajectory associated with serious psychological impairment later in life. Although it is hypothesized that IPV behaviors may spillover into harsh parenting, and thereby influence risk for disruptive behavior, relatively little is known about these processes in families with y… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

7
62
0
4

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 72 publications
(78 citation statements)
references
References 52 publications
7
62
0
4
Order By: Relevance
“…Child externalizing symptoms followed a linear pattern from the low-exposure to polyvictimized classes. These findings reflect the strong link between children's exposure to IPV and disruptive behavior (Evans, Davies, & Dilillo, 2008), which some studies suggest may be mediated by harsh parenting (Grasso, Henry, et al, 2016). Our harsh parenting class findings also highlight risk associated with harsh physical discipline, which was underlined in a recent meta-analysis providing evidence for an adverse effect of spanking on child outcomes, above and beyond physical abuse (Gershoff & Grogan-Kaylor, 2016).…”
Section: Discussionsupporting
confidence: 71%
See 2 more Smart Citations
“…Child externalizing symptoms followed a linear pattern from the low-exposure to polyvictimized classes. These findings reflect the strong link between children's exposure to IPV and disruptive behavior (Evans, Davies, & Dilillo, 2008), which some studies suggest may be mediated by harsh parenting (Grasso, Henry, et al, 2016). Our harsh parenting class findings also highlight risk associated with harsh physical discipline, which was underlined in a recent meta-analysis providing evidence for an adverse effect of spanking on child outcomes, above and beyond physical abuse (Gershoff & Grogan-Kaylor, 2016).…”
Section: Discussionsupporting
confidence: 71%
“…Similar to the clinically-referred Hagan et al (2015) sample, a small, but not unsubstantial, portion of children showed patterns of polyvictimization, characterized by exposure to multiple indicators of psychological and physical violence towards the child and between caregivers. This pattern reflects the high overlap observed between IPV and harsh or abusive parenting (Edelson, 1999; Grasso et al, 2015), which may be due in part to “spillover” of violent behaviors from partner conflict to parent-child interactions (Levendosky & Graham-Bermann, 2001). A second class was likely to have experienced harsh parenting (e.g., spanking) but unlikely to have experienced physical forms of violence between caregivers.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition to heightening risk for a variety of physical and emotional symptoms, the interpersonal nature of child maltreatment and adult violence, which is often manifest in the context of close primary relationships (e.g., abuse perpetrated by a parent or intimate partner violence), may also impact the adult’s capacity to form loving and trusting relationships, to be empathic to others’ distress, and in the case of being a parent, to be sensitive and empathically attuned during interactions with the adult’s own child (Grasso et al 2015; Muzik et al 2013b). Parents who have experienced interpersonal trauma as children or adults are probabilistically more likely to be re-exposed to additional interpersonal violence across their lifespan (Whitfield et al 2003) and they are at greater risk for disrupted parenting sensitivity with subsequent cascading negative effects on their children’s development (Gustafsson et al 2015; Lyons-Ruth and Block 1996).…”
Section: Introductionmentioning
confidence: 99%
“…Na avaliação do fenómeno da exposição da criança aos conflitos interparentais há que ter em conta diversos fatores considerados mediadores do impacto (Overbeek, Schipper, Willemen, Lamers-Winkelman, & Schuengel, 2015;Sani, 2006a), que permitem perceber a variabilidade experiencial destas crianças, a qual se traduz em consequências diversas a curto médio e longo prazos (Almeida & Sani, 2014;Bedi & Goddard, 2007;Grasso et al, 2015;Sani, 2007). Entre estes fatores estão variáveis que apelam às construções cognitivas que cada criança elabora acerca dos conflitos violentos entre os pais (Grych & Fincham, 1990;Grych, Seid & Fincham, 1992;Jouriles, McDonald, Mueller, & Grych, 2013;Mendes & Sani, 2014, 2015 e que influenciam o seu ajustamento global.…”
unclassified